The Distribution of IPO Holdings Across Institutional Mutual Funds - Johnson, William C. (Journal of business ethics, 2009)
We examine initial public offering (IPO) holdings in the mutual funds of four large investment banks and five large non-investment banks during the period 1997 through 2002. Investment banks hold IPOs with different characteristics than IPOs held by non-investment banks, and they also tend to hold IPOs in different types of funds than non-investment banks. We classify holdings as to whether the IPO lies outside or inside the fund’s objective. Investment banks hold IPOs outside the fund objective in 27% of the fund/IPO pairs while non-investment banks hold outside their objective in just 5.4% of fund/IPO pairs. We see significant differences in IPO underpricing for both groups as well. For example, when non-investment banks hold IPOs outside a large capitalization fund objective, they select IPOs with 52% higher underpricing as measured by first-day returns.